2018
DOI: 10.1016/j.ejmg.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approaches to diagnose Diamond-Blackfan anemia: The EuroDBA experience

Abstract: Diamond-Blackfan anemia (DBA) is a rare congenital erythroblastopenia and inherited bone marrow failure syndrome that affects approximately seven individuals in every million live births. In addition to anemia, about 50% of all DBA patients suffer from various physical malformations of the face, hands, heart, or urogenital region. The disorder is almost exclusively driven by haploinsufficient mutations in one of several ribosomal protein (RP) genes, although for ∼30% of diagnosed patients no mutation is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 77 publications
2
55
0
2
Order By: Relevance
“…While an elevated eADA activity is a strong feature of DBA, it is also increased in some leukemias, lymphomas, and immune system disorders 34 . The challenge in performing eADA testing is that the test is not routinely available and is currently performed in only one lab in each of the following countries: the USA, France, Germany, Italy, Poland, Israel, and Turkey 35 . It should be noted that the test needs to be performed on fresh blood samples or samples stored at 4°C for less than a few days and on samples prior to red cell transfusions.…”
Section: Biological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…While an elevated eADA activity is a strong feature of DBA, it is also increased in some leukemias, lymphomas, and immune system disorders 34 . The challenge in performing eADA testing is that the test is not routinely available and is currently performed in only one lab in each of the following countries: the USA, France, Germany, Italy, Poland, Israel, and Turkey 35 . It should be noted that the test needs to be performed on fresh blood samples or samples stored at 4°C for less than a few days and on samples prior to red cell transfusions.…”
Section: Biological Featuresmentioning
confidence: 99%
“…Subsequently, mutations or deletions in 19 other RP genes have been identified by whole exome/genome sequencing and CGH/SNP array. These include RPL5, RPL11, RPL35a, RPS10, RPS24, RPS17, RPL15, RPS28, RPS29, RPS7, RPS15, RPS27a, RPS27, RPL9, RPL18, RPL26, RPL27, and RPL31 as well as three other non-RP genes, TSR2 , GATA1 , and EPO ( Table 1, Figure 1, and 4, 16, 17, 35, 3749 ). It is still debated if the disease associated with non-RP genes is classical DBA or “DBA-like” disease.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Mutations in RPS19 are observed in 25% of DBA patients. Data from the EuroDBA consortium showed that more than 90% of DBA patients are associated with mutations occurring in six DBA genes ( RPS19, RPL5, RPS26, RPL11, RPL35A and RPS24 ) . In addition to mutations in RP genes, two non‐RP genes have recently been reported in DBA patients: GATA1 and TSR2 .…”
Section: Gene Therapy In Inherited Bone Marrow Failure Syndromesmentioning
confidence: 99%
“…The majority (60%) of all heterozygous genetic lesions in DBA involve genes encoding ribosomal proteins (RP), of which 19 (of 80 known RP) genes have been identified so far, including RPS7, RPS10, RPS15A, RPS17, RPS19, RPS24, RPS26, RPS27, RPS28, RPS29 ; RPL5, RPL11, RPL15, RPL18, RPL26, RPL27, RPL31, RPL35, and RPL35A (Da Costa et al , ). In addition, there is a rapidly growing list of new (candidate) genes, including RPL9 (in review), RPL17 (E.E.…”
Section: Diagnosismentioning
confidence: 99%
“…Large international collaborations, including DBAR (http://www.dbar.org) and the EuroDBA network (http://www.eurodba.eu), have proven to be crucial in the ongoing developments in clinical management of DBA and fundamental research. While both national and international collaborations can be challenging, impressive progress has been made with the DBA networks in recent years, and creating a global DBA network is starting to be established (Da Costa et al , ). We therefore encourage clinicians to identify and contribute to networks involved in the care for, and registration of, DBA patients and participate actively in these networks.…”
Section: Future Perspectivesmentioning
confidence: 99%